EVEKTIFITAS HUKUM SISTEM PEMBUKTIKAN ALAT BUKTI ELEKTRONIK DALAM RANAH PEMERIKSAAN BUKTI DI PENGADILAN TATA USAHA NEGARA - Rayhan, Ahmad; Jazuli, E. Rakhmat; Pradita, Essa Alicia; Yuniar, Hafizah Sukma (LPPM Universitas Bina Bangsa, 2024)
Evidence is a tool that can be used for proof to generate the judge's conviction of the true truth. The Constitution of the Republic of Indonesia in 1945 demonstrates a commitment to the constitution, where the Administrative Court is one part of the judicial power that is responsible for examining, deciding, and resolving conflicts related to administrative matters. The development of information and communication technology has brought changes to the judicial system, and one important aspect affected is the use of electronic evidence in the judicial process. Electronic evidence refers to information or data that is stored, transmitted, or received in electronic form. In administrative court proceedings, electronic evidence can take the form of electronic documents, electronic messages, electronic data, or electronic recordings used to prove relevant facts in the ongoing case. However, the use of electronic evidence poses challenges such as the validity and authenticity of electronic evidence, privacy protection, and data security. By using normative juridical research methods, law is conceptualized as what is written in legislation (law in books), or law is conceptualized as rules or norms that serve as standards of human behavior considered appropriate, with an approach to legislation. Therefore, this paper aims to analyze how the system of proving electronic evidence works in administrative court proceedings and the effectiveness of the legal framework for electronic evidence in the realm of evidence examination in administrative court